1992
DOI: 10.3171/jns.1992.76.6.0948
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular compression in trigeminal neuralgia: a clinical and anatomical study

Abstract: Neurovascular decompression is a widely practiced technique for the treatment of trigeminal neuralgia, and yet there is still debate as to whether the beneficial effect results from relieving the nerve of compression by an anatomically abnormal vessel or from the manipulation and trauma the nerve undergoes during the procedure. The development of this operation has been hampered by the lack of adequate anatomical studies in normal controls. The authors present a combined study of clinical and anatomical materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0
7

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(108 citation statements)
references
References 22 publications
5
94
0
7
Order By: Relevance
“…They found that 39 of 41 TN patients had a nerve vessel conflict and the vessel created a groove in the trigeminal nerve. That groove was not present in 50 control subjects, even though 40% of them did show a nerve vessel conflict when physiological blood pressures were applied [Hamlyn and King, 1992]. Unfortunately, modern imaging techniques are unable to pick up this groove within the trigeminal nerve.…”
Section: Diagnosismentioning
confidence: 93%
“…They found that 39 of 41 TN patients had a nerve vessel conflict and the vessel created a groove in the trigeminal nerve. That groove was not present in 50 control subjects, even though 40% of them did show a nerve vessel conflict when physiological blood pressures were applied [Hamlyn and King, 1992]. Unfortunately, modern imaging techniques are unable to pick up this groove within the trigeminal nerve.…”
Section: Diagnosismentioning
confidence: 93%
“…1 A review of autopsy studies reveals some degree of contact between the trigeminal nerve and a blood vessel in 90%-100% of patients with TN, but also in 16%-58% of patients without TN. [16][17][18][19] In 2009, Miller et al, 35 evaluated neurovascular compression (NVC) in patients with and without TN and concluded that trigeminal NVC occurred in asymptomatic patients but was more severe and more proximal in patients with TN. A review of the literature reveals that a wide range (4%-89%) of TN patients has no demonstrable vascular contact.…”
mentioning
confidence: 99%
“…A review of the literature reveals that a wide range (4%-89%) of TN patients has no demonstrable vascular contact. [2][3][4]12,19,24,26,34 For example, Leal et al 26 reported no NVC in 9% of patients by surgical exploration, and imaging revealed no vessel in relation to the nerve in 12% of patients. There are also reports in which all patients have NVC.…”
mentioning
confidence: 99%
“…12,16 In idiopathic TN nerve compression is by a vessel as it exits the medulla oblongata, this theory is supported by the success of MVD in the treatment of compression of trigeminal nerve. 21 TN usually begins as a relapsing disease with pain-free intervals, which sometimes can last for months or years.…”
Section: Discussionmentioning
confidence: 96%
“…8,9 It is shown that in about 96% of cases of typical TN, vascular compression is to be found in only 3% of people without TN, there is a vascular contact with the trigeminal nerve. [10][11][12] The pathological substrate is located in the building of the cranial nerves. In the brain stem the oligodendroglia are responsible for axonal isolation, and outside brain stem is Schwann cells.…”
Section: Introductionmentioning
confidence: 99%